Dr. Pangloss Knows Best - Dennett, Daniel C. (Tufts Archival Research Center, 2005)
Dennett, Daniel C. "Dr. Pangloss Knows Best." Behavioral and Brain Sciences 13 (1990): 581-2. [Also includes original commentary on Dennett by Ron Admundsen].